Academic Supervision Evaluation Practices in Primary Schools: A Case Study of Developmental Leadership - Sri Iin Andriyati; Harjito Harjito; Maryanto Maryanto (Papanda Publisher, 2026)
Academic supervision evaluation plays a crucial role in ensuring the effectiveness of supervisory practices and teacher professional development in primary schools, yet implementation challenges persist globally. This study examined how academic supervision evaluation is implemented by the principal at SD Negeri 1 Plosoharjo, focusing on evaluation mechanisms, guiding principles, and utilization of results for teacher development. A qualitative descriptive case study was conducted with six participants (one principal and five teachers) selected through purposive sampling. Data were collected through in-depth interviews, non-participant observations, and document analysis, then analyzed using systematic data reduction, display, and conclusion drawing. Trustworthiness was ensured through triangulation and member checking. Findings revealed that supervision evaluation was implemented systematically through five interconnected components: observation analysis, document review, individualized feedback, reflective dialogue, and follow-up planning. The evaluation process was characterized by objectivity, transparency, dialogue, and teacher agency. An unexpected finding emerged regarding teachers' active participation in interpreting evaluation results and proposing improvement strategies. Evaluation results were utilized as foundations for targeted professional development activities including coaching, workshops, and collaborative learning. Reflective and continuous evaluation of academic supervision contributes to developing reflective learning cultures and enhancing instructional quality and teacher professionalism in primary schools. The study provides empirical evidence for supervision models that balance accountability with developmental purposes.